Bioethics reflection on life prolongation in end-of-life care - Macedo, João Carlos Gama Martins (2022)
This paper intends to make a bioethics reflection on the prolongation of human life as a consequence of the use of techniques and methods used by current medicine. The term we use is dysthanasia, however, in the anglo-american world the term medical futility is more frequently used, and for this reason we consider it synonymous with the same practice of prolonging human life with the current technical and scientific paraphernalia. The aim of this paper is to find some bioethics guidelines for the best praxis of health professionals in the clinical of end-of-life care.